Howard and Christine Watkins Visit Florence, Italy - Watkins, Howard::::::::: (1988)
Replica statues of Michelangelo's David and of Bartolommeo "Baccio" Bandinelli's Hercules and Cacus in front of the Palazzo Vecchio